2007
DOI: 10.1109/tasc.2007.898535
|View full text |Cite
|
Sign up to set email alerts
|

Tunability of Superconducting Metamaterials

Abstract: Metamaterials are artificial structures with unique electromagnetic properties, such as relative dielectric permittivity and magnetic permeability with values less than 1, or even negative. Because these properties are so sensitive to loss, we have developed metamaterials comprised of superconducting waveguides, wires, and split-ring resonators. An important requirement for applications of these metamaterials is the ability to tune the frequency at which the unique electromagnetic response occurs. In this pape… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
80
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 89 publications
(81 citation statements)
references
References 13 publications
1
80
0
Order By: Relevance
“…This geometrical effect greatly reduces the accumulation of RF currents at the edges of the strip. Moreover, the continuous arc of the spiral allows for a relatively homogenous and uniform flow along the windings compared to sharp-cornered structures that have a tendency to pile up the currents at the corners and edges 16,17 .…”
Section: Methodsmentioning
confidence: 99%
“…This geometrical effect greatly reduces the accumulation of RF currents at the edges of the strip. Moreover, the continuous arc of the spiral allows for a relatively homogenous and uniform flow along the windings compared to sharp-cornered structures that have a tendency to pile up the currents at the corners and edges 16,17 .…”
Section: Methodsmentioning
confidence: 99%
“…Recently, other kinds of tunable metamaterials were also proposed by using, e.g., supercon ductivity and MEMS structures [27,28] as shown in Figure 3(a) and (b). For the supercon ductivity-based metamaterial, the tunability is obtained by changing the external DC or RF magnetic field [27].…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that losses in metamaterials, working in and below the THz frequency range, can be greatly reduced if metallic structures are replaced by superconducting ones [1]. Additionally, superconducting meta-atoms exhibit an intrinsic tunability of their resonance frequency by magnetic field and temperature [2][3][4]. However, in both cases, the tunability arises from a suppression of the superconducting order parameter, i.e.…”
Section: Introductionmentioning
confidence: 99%